Theory-guided design of atomically dispersed dual-metal catalysts for superior oxygen reduction reaction activity - Yang, Yuqi (2023)
The widespread application of electrochemical energy conversion devices, such as proton exchange membrane fuel cells, is hindered by the kinetically sluggish oxygen reduction reaction (ORR) at the cathode. Transition-metal and nitrogen codoped carbon materials (TM−N−C) are among the most promising catalysts to solve this problem. Particularly, dual-metal TM−N−C have already displayed excellent performance. However, further knowledge on the reaction mechanism and the structure−activity relationship is still required. In this study, we established three dual-metal TM−N−C models (FeMn−N−C, FeCo−N−C, and FeNi−N−C) to investigate the electronic interaction between the metallic sites and their corresponding adsorption strength for oxygenated intermediates in ORR electrocatalysis. Then, using density functional theory calculations, we determined that the ORR activity of the dual-metal TM−N−C models followed the order of FeCo−N−C > FeNi−N−C > FeMn−N−C. We confirmed the theoretically predicted activity by synthesizing atomically dispersed FeMn−N−C, FeCo−N−C, and FeNi−N−C catalysts using metal-organic framework precursors, among which FeCo−N−C showed the best results in terms of ORR onset potential and half-wave potential (0.92 and 0.81 V vs. the reference hydrogen electrode in 0.1 M HClO4, respectively.). The results demonstrate the feasibility of the theory-guided rational design of efficient dual-metal catalysts for ORR electrocatalysis.